VD_FINDINFO HC / 2010 / 465 vom 3. September 2010 - VD Tribunal cantonal (2010)
INTERDICTION, PROFESSION, AUTORISATION D'EXERCER, EFFICACITÉ, RÉSILIATION, EXPULSION DE LOCATAIRE, ANNULABILITÉ, DÉLAI LÉGAL | 412 CC, 257d CO, 273 al. 1 CO